2020
DOI: 10.1371/journal.pone.0234348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of viral hepatitis B in Ghana between 2015 and 2019: A systematic review and meta-analysis

Abstract: Chronic hepatitis B (HBV) remains a significant public health problem in Ghana and past reviews conducted could not calculate a nationwide prevalence of the disease due to lack of primary research for some regions of the country. We therefore conducted this study to summarize and update the available information on HBV infection burden (prevalence) in Ghana from 2015-2019.We systematically searched PubMed, Embase, ScienceDirect, and Google Scholar to retrieve primary studies published in peer-reviewed journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 56 publications
8
47
4
Order By: Relevance
“…The Ashanti region had the most studies at 6/21 (29%), while no study was identified for the Upper West region. Across the country, the highest HBV infection prevalence rates were recorded in the age group of 20-40 years [13]. This confirms earlier findings on sero-prevalence of hepatitis B in cirrhosis of the liver in Korle-Bu Teaching Hospital.…”
Section: Practices That Leads To Hepatitis B Transmissionsupporting
confidence: 87%
See 3 more Smart Citations
“…The Ashanti region had the most studies at 6/21 (29%), while no study was identified for the Upper West region. Across the country, the highest HBV infection prevalence rates were recorded in the age group of 20-40 years [13]. This confirms earlier findings on sero-prevalence of hepatitis B in cirrhosis of the liver in Korle-Bu Teaching Hospital.…”
Section: Practices That Leads To Hepatitis B Transmissionsupporting
confidence: 87%
“…Ghana has long been considered to be among the highly endemic countries of sub-Saharan Africa with more than 8% of the population suspected to harbour chronic infection [13]. The review included 21 studies across all ten old regions of Ghana with a total sample population of 29 061 showing recently that the burden of hepatitis B is enormous and remains an important public health issue in Ghana.…”
Section: Practices That Leads To Hepatitis B Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was high risk of HBV infection among young and middle age adults. Other studies in Ghana have identified high prevalence of HBV among young and middle age adults [20,21]. Young and/or middle age adults are more likely to engage in high-risk sexual activities; one of the most frequent routes of transmission for HBV among adults [22].…”
Section: Distribution and Determinants Of Etiologies Of Chronic Livermentioning
confidence: 99%